ADENOID HYPERTROPHY: AN UNUSUAL CAUSE OF NASAL OBSTRUCTION IN ADULTS: Adenoid Hypertrophy - Haq, Anwar ul; Khan, Nasir Ullah; Asghar, Adnan; Manzoor, Faisal; Akhtar, Mohammad; Pervez, Shahid (Pakistan Armed Forces Medical Journal, 2009)
IntroductionAdenoid is collection of lymphoid tissue in the postero-superior wall of the nasopharynx. The term Adenoid hypertrophy indicates non-physiological enlargement of the nasopharyngeal tonsils [1]. This adenoid hypertrophy could be missed because of difficulty of examination of the nasopharynx. We present a rare case of an adult of 22 years of age presented with severe bilateral nasal obstruction due to adenoid hypertrophy.